2008
DOI: 10.1002/mame.200700354
|View full text |Cite
|
Sign up to set email alerts
|

Isotactic Poly(propylene) Nanocomposites Based upon Boehmite Nanofillers

Abstract: The influence of boehmite crystallite sizes, varied between 10 and 60 nm, was studied with respect to the morphology development, crystallization behavior and mechanical properties of the boehmite‐based iPP nanocomposites. The nanometer‐scaled boehmites were formed during twin‐screw melt extrusion of iPP at 200 °C. Even in the absence of polymer compatibilizers, the boehmites, obtained from Sasol's process, enabled very effective deagglomeration and in‐situ dispersion of nanoboehmites. With increase in boehmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 22 publications
5
40
0
2
Order By: Relevance
“…However, the crystallization peak temperature seems to approach a plateau for boehmite content as high as 4 wt%. The nucleating effect of boehmite was already reported in previous papers for polyethylenes [26] and poplypropylene [27], showing a different nucleating efficiency depending on the crystallite size of boehmite nanofiller. Concurrently, the melting temperature recorded during the second scan (T m2 ) is slightly higher for LLDPE nanocomposites, while the crystallinity ($ c ) does not seem to have a direct correlation with the nanofiller addition.…”
Section: Thermal Propertiessupporting
confidence: 62%
See 2 more Smart Citations
“…However, the crystallization peak temperature seems to approach a plateau for boehmite content as high as 4 wt%. The nucleating effect of boehmite was already reported in previous papers for polyethylenes [26] and poplypropylene [27], showing a different nucleating efficiency depending on the crystallite size of boehmite nanofiller. Concurrently, the melting temperature recorded during the second scan (T m2 ) is slightly higher for LLDPE nanocomposites, while the crystallinity ($ c ) does not seem to have a direct correlation with the nanofiller addition.…”
Section: Thermal Propertiessupporting
confidence: 62%
“…When considering LLDPE-boehmite nanocomposites, both T d,onset and T d,max markedly increase with the filler content, showing a slightly higher efficiency in LLDPE-D80 samples. Improved thermal and thermo-oxidative stability due to the addition of BA has been already reported for polyethylenes (PEs) [26] and polypropylene (PP) [27,28]. Nevertheless, future research is required in order to clarify the mechanism of improvement of thermal and thermo-oxidative stability in polyolefines by BA incorporation.…”
Section: Thermal Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…3 for PP and PP/BA40 nanocomposites. Improved thermal and thermooxidative stability due to the addition of BA has been already reported for PEs [19], PP [35,36] and linear low density polyethylene [37]. It was recently demonstrated on LDPE/BA nanocomposites that the improved resistance of the thermooxidative stability due to BA filling is exclusively of physical origin and linked with the barrier effect of the nanoparticles hampering the diffusion of the gaseous degradation products [38].…”
Section: Thermal Propertiesmentioning
confidence: 92%
“…One of the criteria for selecting this filler was that it is water dispersible and thus its nanoscale dispersion can be achieved also in aqueous polymer latex. On the other hand, it was reported that this boehmite alumina can be well dispersed by melt compounding without water as carrier, as well [14].…”
Section: Introductionmentioning
confidence: 98%